(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Hemorrhagic vasculitis capillary toxicosis, also called Henoch-Schönlein disease, is an immunocomplex disease. Hemorrhagic vasculitis or Henoch-Schenelein disease is a disease in which autoimmune damage to small arteries occurs - they become fragile, their permeability increases, which leads to microcirculation, microthrombosis, numerous small hemorrhagic rashes on the skin and mucous membranes, and in internal organs. (gastrointestinal tract, kidneys, joints) causes bleeding. This article discusses the clinical manifestations of hemorrhagic vasculitis.